IMPLEMENTASI BUDAYA MADRASAH DALAM PENGEMBANGAN PENDIDIKAN KARAKTER DI MADRASAH ALIYAH NEGERI 1 BANYUWANGI - Nur Hidayati; Siti Nur Azizah (Institut Agama Islam Darussalam Blokagung, 2022)
Madrasah culture is a madrasah tradition that contains habits that grow and develop following the values adopted and established in madrasah. Character education is a form of effort that is designed and implemented as an effort to improve behavior/speech. Character education itself cannot be formed suddenly. It requires a long process. The process of character formation is one of them starting with habituation. This habituation is called culture. So, in order to form the intended character, it is necessary to build a positive culture in the madrasah environment. This research was conducted at MAN 1 Banyuwangi which has a research purpose: (1) To describe madrasah culture in MAN 1 Banyuwangi and (2) To describe character education and its integration in MAN 1 Banyuwangi. This research uses qualitative methods with qualitative descriptive types while data collection techniques are carried out using interviews, observations, and documentation. Data analysis includes data reduction, data presentation, and inference or verification. Checking the validity is carried out with a triangulation system. Research informants are principals, religious teachers, BK teachers, and students. The results showed that: (1) The implementation of madrasah culture in MAN 1 Banyuwangi includes 8 things, namely wearing Muslim clothes, habituation of prayers jama’ah dhuha and dhuhr, reading dhikr before entering class, tadarus al-Qur'an before lessons, applying 3s (smiles, greetings, and greetings), habituation of adab, ma'had as a supporting madrasah, commemoration of Islamic holidays (2) Implementation of character education in MAN 1 Banyuwangi includes the values of instilled characters, integration of character education in the curriculum, integration of character education in the learning process, integration of character education in routine and extracurricular activities, integration of character education in culture and school environment.